Altered activity-regulated H3K9 acetylation at TGF-beta signaling genes during egocentric memory in Huntington's disease. (December 2022) - Alcalá-Vida, Rafael; Lotz, Caroline; Brulé, Baptiste; Seguin, Jonathan; Decraene, Charles; Awada, Ali; Bombardier, Aurélie; Cosquer, Brigitte; Pereira de Vasconcelos, Anne; Brouillet, Emmanuel; Cassel, Jean-Christophe; Boutillier, Anne-Laurence; et al.
Abstract: Molecular mechanisms underlying cognitive deficits in Huntington's disease (HD), a striatal neurodegenerative disorder, are unknown. Here, we generated ChIPseq, 4Cseq and RNAseq data on striatal tissue of HD and control mice during striatum-dependent egocentric memory process. Multi-omics analyses showed altered activity-dependent epigenetic gene reprogramming of neuronal and glial genes regulating striatal plasticity in HD mice, which correlated with memory deficit. First, our data reveal that spatial chromatin re-organization and transcriptional induction of BDNF-related markers, regulating neuronal plasticity, were reduced since memory acquisition in the striatum of HD mice. Second, our data show that epigenetic memory implicating H3K9 acetylation, which established during late phase of memory process (e.g. during consolidation/recall) and contributed to glia-mediated, TGFβ-dependent plasticity, was compromised in HD mouse striatum. Specifically, memory-dependent regulation of H3K9 acetylation was impaired at genes controlling extracellular matrix and myelination. Our study investigating the interplay between epigenetics and memory identifies H3K9 acetylation and TGFβ signaling as new targets of striatal plasticity, which might offer innovative leads to improve HD. Highlights: Striatum-dependent egocentric memory is early impaired in HD mice. 3D chromatin remodeling is altered during egocentric memory formation in HD mice. H3K9ac-mediated epigenetic memory, contributing to TGFβ-dependent plasticity, is altered during egocentric memory in HD mice.